Influence of ethanol admixture on the determination of equivalence ratios in DISI engines by laser-induced fluorescence - Storch, Michael; Lind, Susanne; Will, Stefan; Zigan, Lars (Applied Optics, 2016)
In this work, the planar laser-induced fluorescence of a fuel tracer is applied for the analysis of mixture formation for various ethanol/iso-octane blends in a direct-injection spark-ignition (DISI) engine. The tracer triethylamine (TEA) was added to pure iso-octane and ethanol as well as to their blends E20 and E85 for the measurement of the fuel/air ratio. In general, ethanol blending strongly affects the mixture formation process, which is caused by specific physical fuel properties influencing the evaporation process of ethanol in comparison to iso-octane. As interactions of the fuel and tracer fluorescence appear possible, TEA fluorescence was studied for different fuel blends in a cuvette, in a calibration cell under constant conditions, and in an optically accessible internal combustion engine at late injection timing. It was found that ethanol blending strongly affects the fluorescence intensity of TEA in the liquid phase, which can be explained by the interaction of the tracer and ethanol molecules. However, in the gas phase a quantification of the fuel/air ratio is possible for different ethanol fuel blends, which is demonstrated in a DISI engine. Under stratified charge conditions the engine results showed a significant impact of a high amount of ethanol on the mixture formation process, leading to a leaner mixture in comparison to iso-octane. (C) 2016 Optical Society of America